Accumulation of Active Species in Silica Mesopore: Effect of the Pore Size and Free Base Additives on Pd‐catalyzed Allylation using Allylic Alcohol. Issue 10 (1st April 2020) - Motokura, Ken; Kawashima, Sae; Nambo, Masayuki; Manaka, Yuichi; Chun, Wang‐Jae
Abstract: A mesoporous silica‐supported Pd complex was prepared using various types of porous silica supports (pore size: 16–31 Å). The effects of the pore size and base additive properties on the catalytic allylation were investigated. The activity of the Pd‐catalyzed allylation of nucleophiles with specific base additives, such as 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU), is strongly affected by the mesopore size. The best allylation performance is obtained with a pore size of 23 Å. On the other hand, bases with smaller/larger molecular size and/or high nucleophilicity, such as K2 CO3 and 1, 4‐diazabicyclo[2.2.2]octane (DABCO), do not seem to show clear pore effect on the catalysis. The performance of the catalytic allylation significantly decreases by using such bases. Kinetic, spectroscopic, and control experiments reveal that the effective accumulation of Pd species and DBU in mesopores with appropriate pore sizes enhances their frequency factors. Abstract : Mesoporous silica : The activity of the Pd‐catalyzed allylation of nucleophiles with specific base additives, such as DBU, is strongly affected by the mesopore size. Kinetic, spectroscopic, and control experiments reveal that the effective accumulation of Pd species and DBU in mesopores with appropriate pore sizes enhances their frequency factors.